Position dependent surface quality in selective laser melting: Positionsabhängige Oberflächenqualität im selektiven Laserstrahlschmelzen. Issue 5 (May 2017) - Hitzler, L.; Hirsch, J.; Merkel, M.; Hall, W.; Öchsner, A.
Abstract: Additive manufacturing receives nowadays opulent attention in both media and ongoing research. In particular, the techniques involving full melting of the raw material, enabling the fabrication of directly deployable components, are of high interest. To date, there are still secondary influences which are yet to be considered, leading to substantial, mainly directional dependent, deviations. The study at hand investigated the surface roughness dependencies in plane, focusing on the interaction of the unidirectional inert gas stream with the irradiation sequence; more precisely the weld splashes emerging from the melt pool, and the resulting in plane pattern. The surface roughness of the upwards orientated faces revealed clear fluctuations, being lowest close to the gas‐inlet and also in the back area of the machine. Perpendicular to the fabrication plane aligned surfaces did not reveal any volatility regarding the inert gas stream. Increasing the energy density of the irradiation led to an increase in the surface roughness of all side faces, but to an improved roughness of the upwards facing surfaces coupled with a significant reduction in evident weld splashes.